Heritability of naevus patterns in an adult twin cohort from the Brisbane Twin Registry: a cross‐sectional study. (1st February 2016) - Lee, S.; Duffy, D.L.; McClenahan, P.; Lee, K.J.; McEniery, E.; Burke, B.; Jagirdar, K.; Martin, N.G.; Sturm, R.A.; Soyer, H.P.; Schaider, H.
Summary: Background: Heritability of naevi counts is widely acknowledged as a potential surveillance parameter for prevention purposes. The contribution of heritability to the changes seen in naevus number and morphology over time and their corresponding dermoscopic characteristics is unknown, but is important to understand in order to account for adequate prevention measures. Objectives: To identify naevus characteristics that are strongly influenced by heritability. Methods: This cross‐sectional study included 220 individuals [76 monozygotic (MZ), 144 dizygotic (DZ)], recruited from the Brisbane Twin Naevus Study. Participants received full body imaging and dermoscopy of naevi ≥ 5 mm in diameter. Dermoscopic type, total naevus count (TNC), change in TNC with age, and naevus distribution, size, colour and profile were compared between MZ and DZ twins. Heritability of these traits was assessed via Falconer's estimate. Results: Significant differences were found in comparing MZ and DZ twins for TNC, numbers of naevi 5·0–7·9 mm in diameter, counts of light‐brown naevi, naevi on the back and sun‐protected sites, and naevi with the 'nonspecific' dermoscopic pattern. Conclusions: This study strongly supports a heritable component to TNC, as well as changes in TNC, and the number of medium‐sized naevi, light‐brown naevi, specific sites and certain dermoscopic features in adults. These characteristics should be taken into account by naevus surveillance programmes and further studied to identify candidate gene associations for clinical and dermoscopic patterns in conjunction with melanoma risk stratification.